MENGGAGAS DESA WISATA PLUNTURAN BERBASIS KEARIFAN LOKAL DI KABUPATEN PONOROGO JAWA TIMUR - Puspaningtyas, Anggraeny; Pramesti, Tri; Lady Rara P., Ingesti; Octaviani, Mita (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
Plunturan is one of villages in Ponorogo, East Java Province. The prime product of Plunturan Village is a cultural heritage that is still maintained by the local village community. The various cultural products are Reyog (Reyog Anak, Reyog Perempuan dan Reyog Taruna); Gajah-Gajahan; Jathilan; Ganongan; Tledekan; Karawitan; Wayang Kulit; Coke’an; Metik Desa; Metri Desa; Metri Tandur; Campursari; and Sego Angkruk. Artists come from across generations, passed down through village elders and art groups. Artists today do not consider the potential of art in their village as their main source of income. They have other livelihoods such as farmers, traders, civil servants, government officials, teachers, health workers, private employees. This condition causes a lack of initiative from artists to attract tourists from outside the region. The role of stakeholders in Plunturan Village is very important in developing cultural tourism. The Tourism Awareness Group (Pokdarwis) which is the driving force for cultural tourism development activities must develop a strategy to make Plunturan a tourism village. Therefore, this service uses a SWOT analysis (strengths, weaknesses, opportunities and treath) to find out what strategies should be taken to initiate Plunturan Tourism Village based on local wisdom. So that culture-based development is not only aimed at improving culture, but also in carrying out development it is necessary to base on the culture that is owned, especially regarding value systems, attitudes and customs.